Seeing is believing (or at least changing your mind): The influence of visibility and task complexity on preference changes in computer‐supported team decision making. (15th June 2015) - Osatuyi, Babajide; Hiltz, Starr Roxanne; Passerini, Katia
Abstract : This article describes an experimental study that examines the extent to which a group decision support system (GDSS), which allows team members to view other members' preference ratings, can encourage changes in individual preferences. We studied 22, four‐person teams performing 2 hidden profile tasks—simple and complex—in a controlled setting. Transparency of the interactions, achieved through the visibility of ratings, influenced changes in participants' preferences as measured before, during and after the team discussion. Visibility of team scores could then offer an effective way to reach consensus, despite individual incumbent preferences. Changes between individuals' initial preferences and team preferences were found to be larger for members working on a complex task compared to a simple task, as were changes between individuals' prediscussion and postdiscussion preferences. Although prior studies established that the initial preferences of individual team members are rather sticky, this study reveals that individuals adjusted their initial preferences to reach a team consensus, as well as modified their preferences after team discussions. Despite the mixed earlier research results on the impact of GDSS on efficient decision making, findings from this study suggest that in complex decision‐making contexts, GDSS tools can be effective in enabling consensus building in groups.